2022
DOI: 10.1186/s12909-022-03562-w
|View full text |Cite
|
Sign up to set email alerts
|

The awareness and practice of testicular self-examination among male undergraduates in Nigeria: a descriptive cross-sectional study

Abstract: Background Testicular cancer is a relatively rare form of cancer but curable. In Nigeria, late presentation hinders treatment due to limited resources for diagnosis and treatment. Testicular self-examination enables men to identify the presence of lumps and any abnormality in their testes. This can facilitate early detection and presentation at hospitals. The purpose of this study was to examine the awareness and practice of testicular self-examination by students at a College of Health Science… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 17 publications
3
11
0
Order By: Relevance
“…There was no definitive knowledge about the prevalence of testicular cancer among various age groups in majority of the subjects under consideration, risk factors, early presentation, and tools for early prevention. All of these findings are consistent with previous literature on awareness, knowledge, and attitudes toward TC [ 2 , 13 - 15 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…There was no definitive knowledge about the prevalence of testicular cancer among various age groups in majority of the subjects under consideration, risk factors, early presentation, and tools for early prevention. All of these findings are consistent with previous literature on awareness, knowledge, and attitudes toward TC [ 2 , 13 - 15 ].…”
Section: Discussionsupporting
confidence: 92%
“…Approximately, 65% of males interviewed did not know that TSE should be done in the shower or shortly after. Eighty-two percent of subjects in our study said that they had not heard about TC, likewise, other studies conducted in other regions showed similar low percentages [ 2 , 7 , 10 , 14 , 15 ]. There was no definitive knowledge about the prevalence of testicular cancer among various age groups in majority of the subjects under consideration, risk factors, early presentation, and tools for early prevention.…”
Section: Discussionsupporting
confidence: 83%
“…3 Despite the fact that TC is a major hazard to health, it is well recognized that early diagnosis can result in improvements of up to 85%-90%, which lowers morbidity. 2,4 Although while certain kinds of TC are asymptomatic until an advanced stage, the majority of TC appear with a tiny lump that may be quickly found by a TSE before the illness has progressed. 5 TSE is a simple screening method that can assist identify abnormal changes in testis tissue and appearance.…”
Section: Background For the Studymentioning
confidence: 99%
“…5 TSE is a simple screening method that can assist identify abnormal changes in testis tissue and appearance. 4,6 For men over the age of 15, TSE is advised to be performed once per month. 6 There is evidence to suggest that men worldwide tend to have some basic knowledge of testicular cancer, but not about TSE.…”
Section: Background For the Studymentioning
confidence: 99%
See 1 more Smart Citation